Photo-generated carriers lose energy during extraction from polymer-fullerene solar cells - Melianas, Armantas; Etzold, Fabian; Savenije, Tom J.; Laquai, Frédéric; Inganäs, Olle; Kemerink, Martijn (Nature Communications, 2015)
Organic photovoltaics rely on the collection of charge carriers generated in disordered materials. Here, the authors unify various experimental techniques and simulations to show that these devices operate out-of-equilibrium, questioning the typical assumption of quasi-equilibrium.